PENGARUH PERMAINAN TEBAK GAMBAR UNTUK MENINGKATKAN PEMAHAMAN KOSA KATA BAHASA ARAB PADA ANAK USIA DINI - Nasrullah; Adhimah, Syifaul (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2024)
This article explores the influence of picture guessing games on improved understanding of Arabic vocabulary in early childhood. Picture guessing, as an interactive and fun learning method, is believed to improve a child's ability to identify and remember new vocabulary. The study used a quantitative approach with experimental design to measure the effectiveness of games in improving children's Arabic vocabulary. The results showed that picture guessing games significantly improved the understanding of speech and improved Arabic language skills in early childhood